PENGARUH KECERDASAN SPIRITUAL, KONSEP DIRI, DAN DUKUNGAN SOSIAL TERHADAP KECEMASAN MENGHADAPI MASA PENSIUN PEGAWAI UNIVERSITAS ISLAM NEGERI RADEN FATAH PALEMBANG - Dewi, Emi Puspita (Program Studi Manajemen Dakwah, Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2019)
Abstract : This research aims to find (1) influence of Spiritual Intelligence, Self Concept, and Social Support simultaneously to the Employee Anxious in Retirement at Raden Fatah State Islamic University of Palembang, dan (2) Influence of Spiritual Intelligence, Self Concept, and Social Support partially to the Employee Anxious in Retirement at Raden Fatah State Islamic University of Palembang. Sample in this research as much 107 persons. Method used in this research is multiple regression model. There are four variables. Those are independent variables which Spiritual Intelligence, Self Concept and Social Support, and also dependent variables is Anxious in Retirement. The analytical tool used is multiple linear regression. According to the research result, find: (1) There is a negative and significant effect Spiritual Intelligence, Self Concept, and Social Support simultaneously to the Employee Anxious in Retirement at Raden Fatah State Islamic University of Palembang, and (2) There is a negative and significant effect Spiritual Intelligence Self Concept, and Social Support partially to the Employee Anxious in Retirement at Raden Fatah State Islamic University of Palembang. Keyword : spiritual intelligence, self concept, social support and anxious in retirement.